2017
DOI: 10.21608/ejh.2017.4074
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Protective Role of Ginger Extract Versus Vitamin E Against Simvastatin-Induced Skeletal Myotoxicity in Adult Male Albino Rats: Histological, Physiological and Biochemical Study

Abstract: Introduction: Statins are group of drugs used to reduce total and low density lipoprotein (LDL)-cholesterol level and to reduce the morbidity and mortality of cardiovascular diseases. Meanwhile, induced skeletal muscle-specific mitochondrial impairment, oxidative stress and myotoxicity are serious side effects . Vitamin E and ginger extract are well known potent antioxidants. Aim: To study the possible protective effect of ginger extract versus vitamin E against simvastatin-induced skeletal muscle histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Additionally, mitochondrial fission (DRP-1 mRNA) trended (p=0.067, Cohen's d=0.45) to be lower in diabetic rats with ginger supplementation. Kawther et al reported that following statin-induced ROS, mitochondria exhibit morphology consistent with unhealthy mitochondria (that is, accumulation of giant mitochondria with destructed cristae) (36). However, in the same study when statins were given ginger supplementation, ginger attenuated statin-induced ROS and improved mitochondrial health (that is, normal sized mitochondria with intact cristae) (36).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Additionally, mitochondrial fission (DRP-1 mRNA) trended (p=0.067, Cohen's d=0.45) to be lower in diabetic rats with ginger supplementation. Kawther et al reported that following statin-induced ROS, mitochondria exhibit morphology consistent with unhealthy mitochondria (that is, accumulation of giant mitochondria with destructed cristae) (36). However, in the same study when statins were given ginger supplementation, ginger attenuated statin-induced ROS and improved mitochondrial health (that is, normal sized mitochondria with intact cristae) (36).…”
Section: Discussionmentioning
confidence: 98%
“…Ginger supplementation scavenges O 2 -(29-31) and has been shown to attenuate muscle atrophy in chemically-induced atrophy rodent models (36,37). Accumulation of oxidative stress (i.e., O 2 -, H 2 O 2 ) results in cellular damage (46), leading to muscle atrophy (7-9, 11, 47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A more precise biomarker reflecting oxidative stress is the OSI pro-oxidant marker, which can reflect an imbalance between antioxidants and pro-oxidation levels as it is defined as the ratio of the TOS level to the TAC level [ 74 ]. Ginger can influence the TAC and TOS ratio and therefore reduce the OSI index through the prevention of oxidation and nitration reactions induced by peroxynitrite, inhibition of xanthine oxidase responsible for the generation of reactive oxygen species, such as superoxide anion or inhibition of NO synthesis [ 75 ].…”
Section: Discussionmentioning
confidence: 99%